الوقف والابتداء في القرآن والاستفادة منهما في تعليم اللغة العربية - UMAR HAQQI; DZUL KHAIDAR (Rayah Al-Islam, 2016)
In fact Arabic and the Qur'an cannot be separated. Therefore, the scholars laid the foundations of the science of waqf and ibtida' to find out the intentions and laws of several qiro'at and differences from both of them to facilitate and raise the difficulties of the ummah when reading the book of Allah. The diversity of meanings causes differences in the place of Waqf according to the reading. As to the number of meanings in the Qur'an with a variety of ways of Waqf and Ibtida’. It is impossible if there is conflict and dispute. This is a type of miracle caused by the difference in meaning according to the way of Waqf and Ibitida' in some qiro'at. This study aims to find out the waqf and ibtida' in the Qur'an in the chapter of Luqman. Arabic students in particular, are required to know waqf and ibtida' in reading the Qur'an and its application in learning Arabic. In completing his thesis, the researcher uses the analysis description method, so the researcher can describe the type of Waqf and Ibtida’ in the chapter of Luqman. Then the researcher explained the benefits of both of them to be used in the method of conversation or text in teaching Arabic. The results of this study show that waqf and ibtida' have an important role in understanding the meaning of Al-Qur'anul-Karim, and the correct way to read it, as well as in teaching Arabic.